Group-based worry intervention for persecutory delusions: an initial feasibility study - Isham, S; Grafahrend, H; Nickless, A; Pugh, K; Pleasants, S; Smedley, N; Freeman, D; Mulligan, A (Cambridge University Press, 2018)
Background: A one-to-one cognitive behavioural therapy intervention targeting worry significantly reduces both worry and persecutory delusions (Freeman et al., 2015). Aim: To adapt this intervention for group delivery and conduct a feasibility trial within routine clinical practice. Method: Thirteen participants were randomized to a weekly 8-session worry intervention group (n = 7) or wait-list control (n = 6). Results: All but one participant completed measures at all time points. Participants attended an average of six therapy sessions. Conclusions: Recruitment, retention and therapy uptake were feasible. Observed treatment effects were in the expected direction, but may be diluted compared with one-to-one interventions.